Critical Reevaluation of Previously Diagnosed Normal Tension Glaucoma Patients- A Three Year Study - Sameer Shahid Ameen, Amjad Akram, Nadia Azad, Salah ud Din Mazhar Ishaq, Amer Yaqub (Pakistan Journal of Ophthalmology, 2006)
Purpose: The objective of this study was to reevaluate the previously diagnosed patients of normal tension glaucoma, visiting Eye Department of Military Hospital Rawalpindi, to confirm whether they really had normal tension glaucoma or not. Material and Methods: All diagnosed normal tension glaucoma patients with routine follow-ups were given a thorough ophthalmic evaluation including best corrected visual acuity, slit lamp examination, stereoscopic disc evaluation using a 90 dioptre lens, Humphrey 30-2 statistic threshold perimetry, central corneal thickness measurement using ultrasonic pachymetry, Goldmann applanation tonometry, and gonioscopy. Visual field testing was carried out using the 30-2 Humphrey field analyser (HFA). Phasing of IOP was done and CT scan and MRI were arranged wherever neuroophthalmological lesions were suspected. After thorough evaluation of each patient and ruling out all other conditions mimicking NTG the actual frequency of normal tension glaucoma was determined. Results: It was found that out of 30 patients evaluated only two patients qualified to be labeled as NTG. Conclusion: If NTG is considered a diagnosis of exclusion chances of making diagnostic mistakes should be minimized. Key Words: Normal tension glaucoma, Applanation tonometry, Central corneal thickness, Intraocular pressure.